Transforming students' perspectives: Boosting biological mathematical attitudes with brain-based learning model - Azzahra, Waliyyatu; Diana, Sariwulan; Nuraeni, Eni (Universitas Negeri Jakarta, 2025)
In the digital era, data and information in biological sciences are increasingly presented in quantitative forms that require processing and analysis, making it essential to train students in numeracy literacy. This study aims to see changes in students' biological mathematical attitudes through the application of the Brain Based Learning Model combined with numeracy literacy tasks. This study used a quasi-experimental method with a pretest-posttest non-equivalent group design. The research sample consisted of 28 students in the experimental class and 30 students in the control class who were selected randomly. The instrument used was a biological mathematical attitude questionnaire with 15 statements on a Likert scale. The results showed that the N-Gain score for students' biological mathematical attitudes was higher in the experimental class with a medium category of 0,51, while in the control class it was in the low category with a score of 0,29. This shows that the Brain Based Learning model is more effective in increasing students' positive attitudes towards the integration of mathematics in biology learning. Based on the results of this study, teachers are expected to consider using the Brain Based Learning Model as a potential alternative learning model, especially in supporting the implementation of the independent curriculum. In addition, it is hoped that other researchers can explore the potential of the Brain Based Learning Model on broader biology topics and other levels of education to expand its positive impact.